Ozone Exposure and Asthma Attack in Children - Huang, Wanting; Wu, Jinzhun; Lin, Xiaoliang (Frontiers in Pediatrics, 2022)
Background Increasing evidence indicated that ozone (O3) exposure could trigger asthma attacks in children. However, the effect of O3 at low concentrations is uncertain. Purpose This study aimed to explore the effects of O3 exposure at low concentrations on asthma attacks in children. Methods A total of 3,475 children with asthma attacks from the First Affiliated Hospital of Xiamen University were available for the analyses. Air pollution data and meteorological data in Xiamen during 2016–2019 were also collected. A case-crossover design and conditional logistic regression models were conducted to evaluate the association between asthma attacks and outdoor air pollution with lag structures (from lag 0 to lag 6) in both single and multi-pollutant models. Furthermore, we estimated the influence of various levels of O3 exposure on an asthma attack in three groups categorized by maximum daily 8-h sliding average ozone (O3-8 h) (O3-8 h ≥ 100 μg/m3, O3-8 h: 80–99 μg/m3, O3-8 h < 80 μg/m3). Results For both single-pollutant models and multi-pollutant models, when O3-8 h was higher than 80 μg/m3, O3 exposure was increased the risk of acute asthma attacks on each day of lag. The effect of O3 on children with asthma was significant when O3 concentration was higher than 100 μg/m3. Conclusion O3 concentration above 80 μg/m3 contributed to an increased risk of asthma attacks in children.